Examining the impact of corporate governance and family ownership on corporate performance: evidence from the Indonesian Stock Exchange - Azwir Nasir; Wan Adibah Wan Ismail; Khairul Anuar Kamarudin; Atika Zarefar; Armadani (Cogent Business & Management, 2024)
This study examines the relationship between corporate governance (CG), family ownership, and corporate performance in firms listed on the Indonesia Stock Exchange (IDX). This research investigates whether CG practices influence both market-based performance (measured by Tobin's Q) and accounting-based performance (measured by Return on Assets, ROA). We further investigate the moderating role of family ownership in this relationship. Our panel data analysis covers the period from 2014 to 2020, including firms from primary and secondary industries. The findings reveal a significantly positive association between CG implementation and corporate performance, indicating that good CG mechanisms enhance a firm's market and accounting performance. However, family ownership weakens this relationship with market performance but has no significant impact on accounting performance. Family-controlled firms tend to exhibit weaker corporate governance practices and may undermine investor confidence, potentially leading to lower stock prices.
Keywords: 650; Corporate governance; family ownership; corporate performance; indonesia; panel data